MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DAN HASIL BELAJAR DI SEKOLAH - Elhefni Elhefni (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2011)
Cooperative learning is learning that requires students to be responsible for himself and his group are responsible for. With cooperative learning students will more easily find and understand difficult concepts if they were in discussions with his students regularly work in groups to help each other in solving complex problems. In cooperative learning are learning techniques of the type of think-pair-share. Type of cooperative learning model think-pair-share it has the advantage that students can be a lot of time to think, respond, and help each other, the teacher only to deliver the material briefly, then ask a question, then the teacher wants students to think more deeply about the material that has been described and experienced. This technique can encourage students to enthusiastic in working together, and by applying a type of cooperative learning model think-pair-share is expected to better learning outcomes for students who learn on their own.